Characteristics of Serum Metabolites and Gut Microbiota in Diabetic Kidney Disease - Bo Zhang; Bo Zhang; Yuzhou Wan; Xuefeng Zhou; Haojun Zhang; Hailing Zhao; Liang Ma; Xi Dong; Meihua Yan; Tingting Zhao; Tingting Zhao; Ping Li (Frontiers Media S.A., 2022)
Disturbance of circulating metabolites and disorders of the gut microbiota are involved in the progression of diabetic kidney disease (DKD). However, there is limited research on the relationship between serum metabolites and gut microbiota, and their involvement in DKD. In this study, using an experimental DKD rat model induced by combining streptozotocin injection and unilateral nephrectomy, we employed untargeted metabolomics and 16S rRNA gene sequencing to explore the relationship between the metabolic profile and the structure and function of gut microbiota. Striking alterations took place in 140 serum metabolites, as well as in the composition and function of rat gut microbiota. These changes were mainly associated with carbohydrate, lipid, and amino acid metabolism. In these pathways, isomaltose, D-mannose, galactonic acid, citramalic acid, and prostaglandin B2 were significantly upregulated. 3-(2-Hydroxyethyl)indole, 3-methylindole, and indoleacrylic acid were downregulated and were the critical metabolites in the DKD model. Furthermore, the levels of these three indoles were restored after treatment with the traditional Chinese herbal medicine Tangshen Formula. At the genera level, g_Eubacterium_nodatum_group, g_Lactobacillus, and g_Faecalibaculum were most involved in metabolic disorders in the progression of DKD. Notably, the circulating lipid metabolites had a strong relationship with DKD-related parameters and were especially negatively related to the mesangial matrix area. Serum lipid indices (TG and TC) and UACR were directly associated with certain microbial genera. In conclusion, the present research verified the anomalous circulating metabolites and gut microbiota in DKD progression. We also identified the potential metabolic and microbial targets for the treatment of DKD.